2005
DOI: 10.1080/00207540500057506
|View full text |Cite
|
Sign up to set email alerts
|

Solution of facility layout problems with pickup/drop-off locations using random search techniques

Abstract: Due to non-polynomial hardness, the facility layout problem (FLP) becomes more critical when pickup/drop-off (P/D) locations are considered in the design of an open field layout under a manufacturing environment. This paper proposes an indigenous model of the facility layout problem based on random search techniques and its solution methodology using a genetic algorithm (GA), simulated annealing (SA) and a hybrid algorithm (HA). The paper illustrates the performance of different random search operating paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Deb and Bhattacharyya (2005) reported that use of GA with SA algorithm (random search hybrid approach) could perform well for layout problems than GA and SA algorithm based methodologies reported in the literature. However, this study differs from Deb and Bhattacharyya (2005) by implementing elitist strategy in ESHGA. To test its effectiveness, problem set 1 and problem set 2 are taken for experimentation and the parameter values are taken from Table 6.…”
Section: Preliminary Experimentsmentioning
confidence: 93%
See 4 more Smart Citations
“…Deb and Bhattacharyya (2005) reported that use of GA with SA algorithm (random search hybrid approach) could perform well for layout problems than GA and SA algorithm based methodologies reported in the literature. However, this study differs from Deb and Bhattacharyya (2005) by implementing elitist strategy in ESHGA. To test its effectiveness, problem set 1 and problem set 2 are taken for experimentation and the parameter values are taken from Table 6.…”
Section: Preliminary Experimentsmentioning
confidence: 93%
“…It consists of four test problem instances of 6 and 12 departments (Welgama and Gibson 1993), 7 departments (Wu and Appleton 2002) and 20 departments (Aiello et al 2002). In addition, to justify the proposed approach, it is compared with the hybrid GA based random search approach that use SA for local search (Deb and Bhattacharyya 2005). The problem set 2 consists of three test problem instances of 12 and 18 departments (Deb and Bhattacharyya 2005) and 62 department problem of Dunker et al (2003).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations